Equities-Capital Market Performance Modelling (ECMP) in Nigeria - Duruechi. Anthony H.; Chigbu. S. U.; Ekweozor, Izunna C. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The work examined equities market operations and capital market performance in Nigeria. It covered the periods 1990 to 2021. Equities market operations were captured by equities market capitalization (ecap), number of listed equities (nole), number of traded equities (note) and value of traded equities (vote). The performance of the capital market on the other hand was encapsulated using market capitalization of the entire market. Data on these variables were obtained from the Central Bank of Nigeria (CBN) and Securities and Exchange Commission (SEC) statistical bulletins. The Autoregressive Distributed Lag (ARDL) approach to cointegration analysis technique aided by the e-views software was used to analyze the data. The result of the study revealed the existence of long-run relationship between equities market operations and performance of the capital market. This led to the conclusion that equities market operations influences capital market performance in Nigeria. Therefore, it was recommended that there is need for increased awareness on the activities of the equities market in Nigeria, promotion of market transparency, confidence in the system and regulatory stability for improved efficiency and effectiveness.